Monitoring (prepoznavanje, spremljanje) in funkcija izbranih koristnih organizmov v nasadih jablan - Zadravec, Peter; Tatjana Unuk, Tatjana Unuk (2023)
Monitoring (Identification, Monitoring) and Function of Beneficial Organisms in Apple Orchards. The professional monography was created during the implementation of the European Innovation Partnership (EIP) 16.5 project entitled Environmental aspects of the transition to organic fruit production. The content is environmentally and sustainably oriented, but still aimed at successful and sufficient production of high–value food. In recent years, we have witnessed the fact that a large number of consumers strongly favor organic food, but at the same time do not want or are unable to pay its slightly higher price. Most growers would like to serve consumers, but are aware of the greater risks stemming from the smaller range and lower effectiveness of plant protection products allowed in organic production. The fact is that satisfactory control of the development of populations of harmful organisms in organic fruit production system is certainly not possible only by replacing plant protection products, therefore the content of this monograph is intended to present the function and monitoring of beneficial organisms in apple orchards as key actors for successful organic fruit production.
Keywords: apple orchard; beneficial organisms; harmful organisms; biodiversity; balance